2001
DOI: 10.1016/s0022-4073(01)00102-9
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated recombination due to resonant deexcitation of metastable states

Abstract: In a recombining plasma the metastable states are known to accumulate population thereby slowing down the recombination process. We show that an account of the doubly-excited autoionizing states, formed due to collisional recombination of metastable ions, results in a significant acceleration of recombination. A fully timedependent collisional-radiative (CR) modeling for stripped ions of carbon recombining in a cold dense plasma demonstrates an order of magnitude faster recombination of He-like ions. The CR mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(74 citation statements)
references
References 31 publications
1
73
0
Order By: Relevance
“…We scanned the plasma volume at distances between 1 mm and 10 mm from the target surface, measuring the absolute intensities and temporal evolution of the Li i 2s-2p, 2p-3d, and 2p-4d transitions. Based on these measurements and using collisional-radiative modeling [21], it was found that the electron density in this plasma region varies between 10 14 and 10 13 cm −3 . For these measurements the spectral overlap of the allowed and the forbidden emissions must be minimized.…”
Section: Methodsmentioning
confidence: 98%
“…We scanned the plasma volume at distances between 1 mm and 10 mm from the target surface, measuring the absolute intensities and temporal evolution of the Li i 2s-2p, 2p-3d, and 2p-4d transitions. Based on these measurements and using collisional-radiative modeling [21], it was found that the electron density in this plasma region varies between 10 14 and 10 13 cm −3 . For these measurements the spectral overlap of the allowed and the forbidden emissions must be minimized.…”
Section: Methodsmentioning
confidence: 98%
“…Calculations of the level populations and line intensities expected from non-Maxwellian plasmas were performed with the collisional-radiative (CR) code NOMAD (Ralchenko & Maron 2001). This code allows modeling of plasma population kinetics for an arbitrary electron energy distribution function and was intensively used in simulations of emission from low-and medium-density plasmas (see, e.g., Arad et al 2000;Gregorian et al 2005).…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…The spectral modeling for the non-Maxwellian EBIT plasma was performed with the collisional-radiative code NOMAD [66] that has been extensively used in EBIT spectroscopy. The yttrium plasma was assumed to be in the steady state, optically thin and uniform with electron density of 10 11 cm −3 .…”
Section: Theoretical Modelingmentioning
confidence: 99%